Research During Foot and Ankle Orthopaedic Fellowship and Association with Careers Following Fellowship. Issue 1 (January 2022) - Patel, Tamanna; Williams, Benjamin R.; Ellis, Scott J.
Category: Other Introduction/Purpose: Performing research during fellowship continues to develop vital critical thinking skills for orthopaedic surgeons as they move into their careers. As fellowships and academic careers become more competitive, research plays an important role in fellow selection and future academic appointments. The purpose of this study was to assess if research during fellowship, measured through journal publications, was associated with careers in academic medicine and if those who published early in their training continued to do so into their careers. Methods: A list of foot and ankle fellows, from 2008-2013, were collected from the AOFAS website. In February 2021, all collected fellows were searched on pubmed.gov to generate all orthopaedic publications with a PubMed identifier published before residency, during residency, during fellowship and after fellowship. Each publication's 2020 Thomson Reuters 5-Year Journal Impact Factor and fellows first authorship were noted. The collected fellows were searched through Doximity.com for the name of their medical school, residency and fellowship. The fellows were further searched for their current location of employment and whether it was academic or not. An employment location was considered academic if they were listed on a department website that also was involved in teaching residents. The number of publications, journal Impact Factor and number of first authorships were compared between the academic and non-academic groups during their time before residency, during residency, during fellowship and after fellowship. Results: A total of 246 fellows were included, with a mean (+- SD) of 0.8 +- 1.4 publications per fellow during fellowship. During the years in review, 27% (67/246) of fellows entered a career in academics. Before residency, there was no difference in the number of publications between those that went into academic and those that did not [academics 0.54 +- 1.85, non-academic 0.27 +- 1.05 (p=0.154)]. During residency and fellowship, those that went into academics were statistically significantly more likely to publish than those that did not go into academics [during residency: academic 2.82 +- 4.53, non-academic 1.24 +- 2.00 (p=0.0002); during fellowship: academic 1.10 +- 1.57, non-academic 0.69 +- 1.34 (p=0.038)] as well as more first authorships and in journals with higher impact factors. Conclusion: As fellowships and academic positions become more competitive, the quality and number of journal publications are likely to become increasingly more important. This study noted that an interest in academics likely develops during orthopaedic residency. This study may help improve mentorship earlier on to those who are more likely to pursue a career in academics.